2011
DOI: 10.1080/13691457.2010.487411
|View full text |Cite
|
Sign up to set email alerts
|

Does social workers’ personal experience with violence in the family relate to their professional responses, and how?

Abstract: Does social workers' personal experience with violence in the family relate to their professional responses, and how?Djeluje li privatno iskustvo s nasiljem u obitelji na stručne reakcije socijalnih radnica i kako?Ali osebna izkušnja z nasiljem v druž ini vpliva na strokovne reakcije socialnih delavk in kako?The study examines if and how social workers' personal experience with violence in the family relates to their professional responses to children's exposure to domestic violence and physical abuse. Four ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(19 reference statements)
0
7
0
1
Order By: Relevance
“…In addition, when a social problem is widespread and pervasive as the statistics show, it may not be surprising to find persons in social work classrooms and agencies with personal experiences of intimate partner violence against women that mirror those of clients. While Pecnik and Bezensek-Lalic (2011) suggest that a seeming "disengagement strategy" could reflect practitioners' struggles with their own histories, this study did not provide opportunities for participants to disclose these. Darling (2007) observed that at the micro-level, persons make sense of their experiences and shape environments through their actions and interactions, and a link can be made between practitioners' perceptions of futility in practice, their consequent frustrations, and their views of victims and victimization.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, when a social problem is widespread and pervasive as the statistics show, it may not be surprising to find persons in social work classrooms and agencies with personal experiences of intimate partner violence against women that mirror those of clients. While Pecnik and Bezensek-Lalic (2011) suggest that a seeming "disengagement strategy" could reflect practitioners' struggles with their own histories, this study did not provide opportunities for participants to disclose these. Darling (2007) observed that at the micro-level, persons make sense of their experiences and shape environments through their actions and interactions, and a link can be made between practitioners' perceptions of futility in practice, their consequent frustrations, and their views of victims and victimization.…”
Section: Discussionmentioning
confidence: 88%
“…Danis (2004) and Warrener et al (2013) show, unsurprisingly, that professional self-efficacy was significantly higher among social workers who had more professional experience working with intimate partner violence against women, and specific education and/or training in this area. Pecnik and Bezensek-Lalic (2011), in a study in Slovenia, explored the relationship between social workers' personal history of childhood abuse and witnessing intimate partner violence against women between their parents, and their responses to case vignettes of intimate partner violence against women. The researchers found a positive correlation with safeguarding instincts for children, but a negative correlation with referrals to police and shelters for victims.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These results are in line with previous research showing that attitudes of professionals toward the removal of the child are related to their decision-making (Davidson-Arad & Benbenishty, 2016). A professional’s perception of an out-of-home placement as harmful has been explained by professional’s personal experience with child maltreatment or neglect in his or her own life or in working with previous families (Pecnik & Bezensek-Lalic, 2011). Although the amount of work experience has not been shown to be related to out-of-home placement decisions, the type of experience professionals had with previous families and in their own family may explain how harmful they perceive an out-of-home placement (Pecnik & Bezensek-Lalic, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other research suggests that childhood adversity predicts altered, if not necessarily impaired, professional judgement. Compared to their colleagues, family protection workers with childhood experiences of domestic violence and abuse have been found less likely to recommend that victims seek police intervention (Pecnik & Bezensek, 2011), and more likely to believe testimonies from child victims (Nuttall & Jackson, 1994). Preliminary evidence suggests that a worker's lived experience influences how they will perceive their clients and how they will make professional judgements.…”
Section: Introductionmentioning
confidence: 98%